PENGARUH KUALITAS PELAYANAN TERHADAP MOTIVASI KERJA MELALUI TRANSPARANSI PADA DINAS PENANAMAN MODAL DAN PERIZINAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN TABALONG (JAPB, 2022)
This study aimed to determine how much service quality influences work motivation through transparency at the One Stop Integrated Licensing and Investment Service (DPMPTSP) Tabalong Regency. This type of research is quantitative. Therefore, the researcher uses a quantitative approach to process data and facts to fulfil research objectives. The research approach is a design procedure and plan that begins step by step with hypotheses that continue in data collection, analysis and conclusions to create a detailed picture of the events studied—narrative descriptive or numerical measurement. The population and sample in this study were visitors and the public who managed permits at the One Stop Integrated Licensing and Investment Service (DPMPTSP) Tabalong Regency, with as many as 69 people. The data collection techniques were observation, questionnaires and documentation—the analytical method used using the Sobel test method, according to Preacher and Hayes, 2004. The results of this study indicate that the Effect of Service Quality on Work Motivation through Transparency at the One Stop Integrated Licensing and Investment Service (DPMPTSP) Tabalong Regency obtained an effect of 10.24 %. Keywords: Service Quality, Work Motivation, Transparency